2019
DOI: 10.3390/cells8080786
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Nervonic Acid Ester Improves Myelin Synthesis by Human Oligodendrocytes

Abstract: The dysfunction of oligodendrocytes (OLs) is regarded as one of the major causes of inefficient remyelination in multiple sclerosis, resulting gradually in disease progression. Oligodendrocytes are derived from oligodendrocyte progenitor cells (OPCs), which populate the adult central nervous system, but their physiological capability to myelin synthesis is limited. The low intake of essential lipids for sphingomyelin synthesis in the human diet may account for increased demyelination and the reduced efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 53 publications
(66 reference statements)
0
43
0
1
Order By: Relevance
“…To produce nervonoyl-CoA, the SCD2 product oleoyl-CoA is subsequently elongated by elongase-1 three times [ 56 ]. Thus, in mice, SCD2 predominately carries out the rate-limiting step of nervonoyl-CoA (C24:1n9) biosynthesis in oligodendrocytes [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To produce nervonoyl-CoA, the SCD2 product oleoyl-CoA is subsequently elongated by elongase-1 three times [ 56 ]. Thus, in mice, SCD2 predominately carries out the rate-limiting step of nervonoyl-CoA (C24:1n9) biosynthesis in oligodendrocytes [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In MS patients and experimental autoimmune encephalomyelitis rodents used as a model for MS, both sphingomyelin and nervonoyl-CoA are significantly decreased compared to control samples [ 57 , 58 ]. These data suggest that SCD2 is a critically important enzyme that controls the supply of nervonoyl-CoA (C24:1n9) for myelin biosynthesis and that inhibition of SCD2 may significantly contribute to MS [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Impairment of NA provision has been found in the postmortem brains of individuals with demyelinating diseases such as X-ALD and MS and has been suggested as a cause of pathogenesis in these diseases 8 . Experiments using EAE mice, an animal model for MS, revealed that during acute inflammation, NA synthesis was inhibited with a shift to the synthesis of proinflammatory arachidonic acid 19 . In vitro assays of NA-containing fish oil added to cultured human oligodendrocyte precursor cells led to an enhanced maturation rate of the cells and increased synthesis of sphingomyelin.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro assays of NA-containing fish oil added to cultured human oligodendrocyte precursor cells led to an enhanced maturation rate of the cells and increased synthesis of sphingomyelin. In addition, NA-containing oil was shown to inhibit the secretion of several proinflammatory factors while promoting growth factor synthesis, which is important for the regeneration of the CNS 19 . Therefore, it is sug-gested that dietary therapy with NA-rich oil may be beneficial for these neurodegenerative diseases 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipid profiling in the brain of EAE mice revealed that during acute inflammation, nervonic acid synthesis is inhibited, with a shift of lipid metabolism pathway of common substrates into proinflammatory arachidonic acid production. Although its remyelinating potential has not been evaluated, cultured human OPCs exposed to nervonic acid increased their maturation rate and the synthesis of sphingolipids [25], suggesting that changing the composition of lipid metabolism may be an important and overlooked prerequisite for remyelination.…”
Section: Figurementioning
confidence: 99%